The muscle-bone interaction in Turner syndrome - Soucek, Ondrej; Matyskova, Jana; Anliker, Elmar; Toigo, Marco; Hlavka, Zdenek; Lebl, Jan; Sumnik, Zdenek (Bone, 2015)
OBJECTIVES: Turner syndrome (TS) is associated with an increased fracture rate due to reduced bone strength, which is mainly determined by skeletal muscle force. This study aimed to assess the muscle force-bone strength relationship in TS and to compare it with that of healthy controls. METHODS: This study included 39 girls with TS and 67 healthy control girls. Maximum muscle force (Fmax) was assessed through multiple one-legged hopping with jumping mechanography. Peripheral quantitative computerized tomography assessed the bone strength index at the tibial metaphysis (BSI 4) and the polar strength-strain index at the diaphysis (SSI polar 66). The effect of TS on the muscle-bone unit was tested using multiple linear regression. RESULTS: TS had no impact on Fmax (p=0.14); however, a negative effect on bone strength (p<0.001 for BSI 4 and p<0.01 for SSI polar 66) was observed compared with healthy controls. Bone strength was lower in the TS group (by 18%, p<0.01, for BSI 4 and by 7%, p=0.027, for SSI polar 66), even after correcting for Fmax. CONCLUSIONS: Similar muscle force induces lower bone strength in TS compared with healthy controls, which suggests altered bone-loading sensitivity in TS.
Keywords: Muscles; Anthropometry; Muscle force; antropometrie; Humans; Case-Control Studies; Ovarian function; Turner syndrome; studie případů a kontrol; svaly; Bone strength indices; Female; Bone and Bones; kosti a kostní tkáň; lidé; ženské pohlaví; Muscle–bone unit; Turnerův syndrom; Adolescent; Turner Syndrome; biomechanika; Biomechanical Phenomena; mladiství